2012
DOI: 10.1590/s0102-695x2011005000213
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antimicrobial activities of the leaf essential oil of Machilus zuihoensis from Taiwan

Abstract: This study investigated the chemical composition, and antimicrobial and anti-wood-decay fungal activities of the essential oil isolated from the leaf of endemic Machilus zuihoensis Hayata, Lauraceae, of Taiwan. The essential oil from the fresh leaves of M. zuihoensis was isolated using hydrodistillation in a Clevenger-type apparatus, and characterized by GC-FID and GC-MS. A total of 104 compounds were identified, representing 100% of the oil. The main components identified were n-dodecanal (23.8%) and (E)-nero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…The antimicrobial activity of an essential oil is attributed mainly to its major compounds; however the synergistic or antagonistic effect of a minor component of the complex mixture has to be considered. Others studies showed antimicrobial activity with oil containing at least one of these major oil compounds as the principal component (Hisham et al, 2006;Mevya et al, 2007;Asfaha et al, 2008;Ho et al, 2009). The results showed that Gram-positive bacteria S. pneumoniae was more sensitive than Gram-negative FIGURE 1.…”
Section: Antimicrobial Activitymentioning
confidence: 98%
“…The antimicrobial activity of an essential oil is attributed mainly to its major compounds; however the synergistic or antagonistic effect of a minor component of the complex mixture has to be considered. Others studies showed antimicrobial activity with oil containing at least one of these major oil compounds as the principal component (Hisham et al, 2006;Mevya et al, 2007;Asfaha et al, 2008;Ho et al, 2009). The results showed that Gram-positive bacteria S. pneumoniae was more sensitive than Gram-negative FIGURE 1.…”
Section: Antimicrobial Activitymentioning
confidence: 98%
“…After liquid-liquid extraction, high levels of these sesquiterpenes were found in GPH and BPH. Nerolidol, δ-cadinene, γ-muurolene, caryophyllene and its derivative caryophyllene oxide are naturally occurring sesquiterpenes found in the essential oils of many types of plants Ho, Liao, & Su, 2012;Senatore et al, 2013), but also in green propolis samples (De Albuquerque, Alves, Lemos, Dorneles, & De Morais, 2008;Torres, Lopes, Neto, & Citó, 2008). The chemical composition of the essential oil obtained by hydrodistillation of green propolis has been analyzed by GC-FID and GC/MS (De Albuquerque et al, 2008).…”
Section: Overall Variation In Metabolite Composition Of Propolis Samplesmentioning
confidence: 99%
“…Recent studies also demonstrated that both α-pinene and β-pinene have antioxidant properties by 2,2-diphenyl-1-picrylhydrazyl, hydroxyl (OH) radical, superoxide anion (O2 − ), malonaldehyde/gas chromatography, aldehyde/carboxylic acid, and β-carotene bleaching methods (Wei et al 2007;Wang at al. 2008;Singh et al 2009;Ho & Su 2012).…”
Section: Primary Rat Neuronsmentioning
confidence: 99%